Comparison of Gonadotropin-Releasing Hormone versus Estrogen-Based Fixed-Time Artificial Insemination Protocols in Grazing Bos taurus Suckled Beef Cows - Ferre, Luis Bernardo; Jaeschke, Julian; Gatti, Juliana; Baladón, Gerardo; Bellocq, Ezequiel; Fernández, Gustavo; Rearte, Ramiro; Kjelland, Michael E.; Colazo, Marcos G.; Thomas, Jordan M. (MDPI, 2023)
Fixed-timed artificial insemination (FTAI) protocols for beef cattle in South America are primarily based on estradiol esters and intravaginal progesterone-releasing devices (IVPD). The objective of this study was to determine the optimal gonadotropin-releasing hormone (GnRH)-based protocol as an alternative to the use of estrogen-based protocols in grazing Bos taurus suckling beef cows. All cows received an IVPD on the day of protocol initiation and prostaglandin F2α (PG) plus equine chorionic gonadotropin (eCG) treatments at the time of IVPD removal. In Experiment 1, cows (n = 235) were randomly assigned to one of four treatments: (i) 7-day estradiol = 2 mg of estradiol benzoate (EB) at IVPD insertion on Day 9 and 1 mg of estradiol cypionate (ECP) at IVPD removal on Day 2; (ii) 7-day GnRH = 10 µg of GnRH at IVPD insertion on Day 10, IVPD removal on Day 3 and GnRH at FTAI; (iii) 7 & 7 estradiol = PG at IVPD insertion on Day 16, EB on Day 9 and ECP at IVPD removal on Day 2; (iv) 7 & 7 GnRH = PG at IVPD insertion on Day 17, GnRH on Day 10, IVPD removal on Day 3 and GnRH at FTAI. In Experiment 2, cows (n = 462) were randomly assigned to one of four treatments: (i) 6-day estradiol = EB at IVPD insertion on Day 9, IVPD removal on Day 3 and GnRH at FTAI; (ii) 7-day estradiol; (iii) 7-day GnRH; (iv) 7 & 7 GnRH. In Experiment 1, plasma progesterone concentrations and percentage of cows with a corpus luteum (CL) at IVPD removal, and pregnancy per AI (P/AI) were greater for cows subjected to GnRH-based protocols compared with cows subjected to estrogen-based protocols (p < 0.01). In Experiment 2, cows subjected to the 7 & 7 GnRH protocol had the greatest P/AI (p < 0.01). In summary, GnRH-based FTAI protocols resulted in similar or greater P/AI compared to estrogen-based FTAI protocols in grazing postpartum Bos taurus suckled beef cows. The greatest P/AI was attained with the 7 & 7 GnRH protocol.